Husserl e l’empiriocriticismo. L’interrelazione tra io, corpo e mondo nella costituzione dell’esperienza - Fugali, Edoardo (Bollettino Filosofico, 2024)
The contribution investigates the influence of Avenarius and Mach’s empiriocriticism on Husserl’s phenomenology. Despite his critical reservations, Husserl acknowledges the role of both in anticipating his phenomenological method and appreciates their critique of materialistic metaphysics and the prevailing physicalism in psychology. Phenomenology and empiriocriticism share the goal of a science of conscious experience, free from reductionism and capable of preserving the specificity of its object. Husserl adopts Mach’s analyses of the living body and spatial sensations, developing a phenomenology of kinesthesia in which transcendental consciousness, body, and world are fully integrated. This approach influences his theory of constitution, aimed at overcoming Cartesian dualism and adequately accounting for the subject’s rootedness in the world. Keywords: Empiriocriticism, Lived Body, Natural World, Phenomenology, Transcendental Consciousness